Legal Protection for Public Housing Loan Customers Under Law No. 8 of 1999 on Consumer Protection in Housing Transactions - Fazri Editiya Mahardika; Deny Guntara; Muhamad Abas (PT. Anagata Sembagi Education, 2024)
Public housing credit is a program aimed at addressing the housing backlog in Indonesia, yet its implementation faces various challenges. This research focuses on two main issues: (1) What happens to public housing loans when banks go bankrupt? (2) How can consumer issues be resolved when housing loans default? The study uses a normative judicial method. The findings reveal that while the People's Housing Credit (KPR) helps people acquire homes, significant risks arise if credit institutions go bankrupt or debtors default. In cases of default or bank bankruptcy, debtors must still fulfill their credit obligations. Consumer protection is outlined in the 1999 Consumer Law, which includes exit clauses in credit agreements. The government, through the Deposit Insurance Corporation (LPS), can rescue or liquidate banks according to Law No. 24 of 2004. Moreover, drafting fair contracts, offering credit restructuring, and providing insurance options can better protect debtors than asset auctions. Additionally, applying the principle of prudence in credit assessments, as per the Banking Law, is crucial to minimizing default risks. Stricter regulations and robust legal protections are essential for mortgages to effectively help people own homes while ensuring financial and legal stability.